Physiological acclimation and persistence of ectothermic species under extreme heat events. Issue 7 (15th April 2019) - Morley, S. A.; Peck, L. S.; Sunday, J. M.; Heiser, S.; Bates, A. E.
Abstract: Aim: To test if physiological acclimation can buffer species against increasing extreme heat due to climate change. Location: Global. Time period: 1960 to 2015. Major taxa studied: Amphibians, arthropods, brachiopods, cnidarians, echinoderms, fishes, molluscs, reptiles. Methods: We draw together new and existing data quantifying the warm acclimation response in 319 species as the acclimation response ratio (ARR): the increase in upper thermal limit per degree increase in experimental temperature. We develop worst‐case scenario climate projections to calculate the number of years and generations gained by ARR until loss of thermal safety. We further compute a vulnerability score that integrates across variables estimating exposure to climate change and species‐specific tolerance through traits, including physiological plasticity, generation time and latitudinal range extent. Results: ARR is highly variable, but with marked differences across taxa, habitats and latitude. Polar terrestrial arthropods show high ARRs [95% upper confidence limit (UCL95%) = 0.68], as do some polar aquatic invertebrates that were acclimated for extended durations (ARR > 0.4). While this physiological plasticity buys 100s of years until thermal safety is lost, combination with long generation times leads to decreased potential for evolutionary adaptation. Additionally, 27% of marine polar invertebrates have no capacity for acclimation and reptiles and amphibians have minimal ARR (UCL95% = 0.16). Low physiological plasticity, long generations times and restricted latitudinal ranges combine to distinguish reptiles, amphibians and polar invertebrates as being highly vulnerable amongst ectotherms. Main conclusions: In some taxa the combined effects of acclimation capacity and generation time can provide 100s of years and generations before thermal safety is lost. The accuracy of assessments of vulnerability to climate change will be improved by considering multiple aspects of species' biology that, in combination may increase persistence under extreme heat events, and increase the probability for evolutionary rescue.